First look for the fundamental solutions by solving the homogeneous version of the ODE:

The characteristic equation is

with roots
and
, giving the two solutions
and
.
For the non-homogeneous version, you can exploit the superposition principle and consider one term from the right side at a time.

Assume the ansatz solution,



(You could include a constant term <em>f</em> here, but it would get absorbed by the first solution
anyway.)
Substitute these into the ODE:




is already accounted for, so assume an ansatz of the form



Substitute into the ODE:





Assume an ansatz solution



Substitute into the ODE:



So, the general solution of the original ODE is

Answer:
$125.2-discount
$500.8-sale price
Step-by-step explanation:
hope it helps
Answer:
40 percent increase
Step-by-step explanation:
Starting point - 95
End point - 133
133-95 = 38
38/95 = 0.4
0.4*100=
40
3x²–243=0 —> 3 (x²–81) = 0 —>
x²–81=0 —> (x-9)(x+9)=0
x-9=0 —> x=9
x+9=0 —> x=–9
I hope I helped you^_^